Do Political Parties Matter for Local Land Use Policies? - Albert Solé-Ollé; Elisabet Viladecans-Marsal (Center for Economic Studies and ifo Institute (CESifo), 2013)
Despite interest in the impact of land use regulations on housing construction and housing prices, little is known about the drivers of these policies. The conventional wisdom holds that homeowners have an influence on restrictive local zoning. In this paper, we contend that the party controlling local government might make a major difference. We draw on data from a large sample of Spanish cities for the 2003-2007 political term and employ a regression discontinuity design to document that cities controlled by left-wing parties convert much less land from rural to urban uses than is the case in similar cities controlled by the right. The differences between governments on the two sides of the political spectrum are more pronounced in places with greater population heterogeneity and in those facing higher housing demand. We also present some results suggesting these partisan differences might ultimately impact on housing construction and housing price growth.
Keywords: R52; 330; land use regulations; urban growth controls; political economy